PERANCANGAN EA (EXPER ADVISOR) UNTUK TRADING FOREX DENGAN BAHASA MQL4 - Aulia, Aldi; Priyatna, Bayu; Hananto, Agustia; Hananto, April Lia; Tukino, Tukino (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The research was conducted to create an expert advisor who can interact with the forex market automatically using the MQL4 language. Expert Advisor System is a design that consists of an array of technical analysis algorithms and indicators. The exponential moving average indicator is used in the creation of trading robots or better known as expert advisors. In designing this expert advisor, it starts with the process of making coding, implementing or designing coding, as well as testing GBP / USD and EUR / USD. In this study, the design of expert advisors that have been designed creates a system that facilitates and helps traders to trade foreign currencies. Based on the design by backtesting from January 1, 2022 to May 1, 2022 with a capital of 10000 USD, with GBP/USD pair, 4H timeframe, 1:100 laverage and EUR/USD M15 timeframe pair, leverage of 1:100 can generate a total net profit for GBP/USD of -43.81 and for a total net profit of EUR/USD of -16.35. The output of this study concluded that the use of moving averages is the basis for expert advisor logic to assist in making trading decisions even though the results have not been maximized.